2016
DOI: 10.1002/cjp2.40
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence imaging to localize head and neck squamous cell carcinoma for enhanced pathological assessment

Abstract: Accurately identifying close or positive margins in real‐time permits re‐excision during surgical procedures. Intraoperative assessment of margins via gross examination and frozen section is a widely used tool to assist the surgeon in achieving complete resection. While this methodology permits diagnosis of freshly resected tissue, the process is fraught with misinterpretation and sampling errors. During fluorescence‐guided surgery, an exogenous fluorescent agent specific for the target disease is imaged in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…We showed that 5 mg of tumor could be identified in the clinical setting as shown in Fig. ; this exceeds current detection thresholds reported in the literature …”
Section: Opportunities For Optical Imaging Throughout the Patient's Msupporting
confidence: 47%
See 1 more Smart Citation
“…We showed that 5 mg of tumor could be identified in the clinical setting as shown in Fig. ; this exceeds current detection thresholds reported in the literature …”
Section: Opportunities For Optical Imaging Throughout the Patient's Msupporting
confidence: 47%
“…From the studies, intravenous administration of fluorescently labeled anti‐EGFR antibody can image cutaneous and mucosal squamous cell carcinoma in vivo and ex vivo and throughout histology processing since the dye is not significantly degraded by formalin fixation and paraffin embedding . Using a range of devices as listed in T, the tissue can be imaged at each step–intraoperatively or in the clinic (Fig.…”
Section: Opportunities For Optical Imaging Throughout the Patient's Mmentioning
confidence: 99%
“…Results from a recent clinical trial of cetuximab‐IRDye800CW demonstrated sufficient specificity to fluorescently localize disease in HNSCC patients . Using this antibody‐based method, fluorescence contrast delivers a more sensitive and specific approach when compared to a surgical and pathological evaluation . When compared to standard histopathological evaluation, florescence imaging has the potential to permit evaluation of the entire wound bed, which could greatly reduce sampling error.…”
Section: Discussionmentioning
confidence: 99%
“…2LMP cells incubated Using this antibody-based method, fluorescence contrast delivers a more sensitive and specific approach when compared to a surgical and pathological evaluation. 20 When compared to standard histopathological evaluation, florescence imaging has the potential to permit evaluation of the entire wound bed, which could greatly reduce sampling error. Accurate localization is further supported at the cellular level as histologic assessment of florescence sequestration demonstrates a statistically significant (P < 0.001) delineation between cancerous/non-cancerous tissues at 1 mm from the tumor border.…”
Section: Effect Of Incubation Time On Disease Detectionmentioning
confidence: 99%
“…Clinical applications of tumor-specific fluorescent dyes under trials currently include fluorescent folate to label ovarian cancer and fluorescent cetuximab to label head and neck cancers, but data on survival advantage and rate of tumor recurrence are not yet available (23,24). The number of fluorescence labeling platforms will greatly increase in the future along with further data on their impact of oncologic outcomes.…”
mentioning
confidence: 99%